Concise Synthesis of a Cyclopentane Intermediate Possessing All Nitrogen Functionalities for Pactamycin - Matsumoto, Nobuyuki; Nakazaki, Atsuo; Nishikawa, Toshio (Synlett, 2017)
Pactamycin, a potent antitumor and antimicrobial antibiotic, possesses a densely functionalized cyclopentane core structure. This paper describes the concise synthesis of an advanced intermediate for synthesizing the enantiomer of pactamycin that contains the cyclopentane skeleton bearing all the necessary amino functions with correct stereochemistries.
Keywords: natural product synthesis; pactamycin; aminocyclopentitol; oxime–olefin cycloaddition; aziridines